Understanding Software Developer Activity via Windows 10 Telemetry - Buja, Spencer; Zimmermann, Tom; Kirsanov, Philippe; Tandon, Ankit; Liu, Xue; Windsor, Jay; Addis, Henok (Microsoft, 2019)
Over the past several decades, businesses and the U.S. economy have become increasingly dependent on non-routine cognitive work. Business managers and researchers agree that it is difficult to measure and quantify productivity for this type of work, commonly referred to as “knowledge work”. Both startups and large enterprises must be able to analyze the productivity of their knowledge workers in order to thrive, as “knowledge work” becomes more prevalent. At Microsoft, most of the “knowledge work” is produced by software engineers that write code. Using novel data from the Windows 10 Operating System (OS), we have developed and tested hypotheses about how software engineers work and how to improve their experience. We demonstrate how this people analytics data is ethically collected, labeled, and analyzed to guide product and organizational decisions at Microsoft. Finally, we discuss the considerations and ethics of passively collecting productivity data.
Presented at the 2019 Wharton People Analytics Conference. Finalist for the White Paper Competition